PENGARUH PERPUTARAN PERSEDIAAN VOUCHER SEV DALAM MENINGKATKAN LABA OPERASI PT. ELKOMINDO MITRA NUSANTARA BENGKULU - -, Herlin (Universitas Dehasen Bengkulu, 2014)
Herlin; Inventory is the most active part in the companys operations, which continually purchased or manufactured or sold. Turnover of inventory (inventory turnover) measures the relationship between the volume of merchandise sold by the amount of inventory on hand during the period. Inventory is very important for any company, in the absence of an adequate supply of the company is not able to meet customer desires, so that the companys inventory management should be carried out effectively and efficiently. This study aimed to examine the effect of the merchandise inventory turnover increase operating profit of PT. Mitra Nusantara Elkomindo Bengkulu. The sample in this study is the inventory voucher SEV PT. Mitra Nusantara Elkomindo Bengkulu observation period of 3 years. Inventory turnover during 2010, 2011 and 2013 has increased for each year showing that the higher the inventory turnover increased operating profit meal, this proves that the inventory turnover vouchers SEV gives positive effect in increasing the operating profit of PT. Mitra Nusantara Elkomindo Bengkulu Â Key words:Inventory Turnover, Operating Profit